Domestic Organic Waste: A Potential Source to Produce the Energy via a Single-Chamber Microbial Fuel Cell - Amira Suriaty Yaakop; Akil Ahmad; Fida Hussain; Sang-Eun Oh; Mohammed B. Alshammari; Raju Chauhan (International Journal of Chemical Engineering)
Microbial fuel cell (MFC) is a method that is both effective and environmentally friendly for producing renewable electricity. Several studies have shown that one of the major challenges is the generation of electrons as a result of poor exploitation of organic substrates. One of the most talked about issues in modern molecular fusion is the reutilization of biological organic waste in an MFC. In this article, the effective utilization of domestic organic waste as an organic supply for bacterial species to generate energy was highlighted. The findings that were obtained corresponded to the one-of-a-kind MFC operation in which a voltage of 110 mV was generated in a time span of 12 days during operation with an external resistance of 500 ῼ. With an internal resistance of 117 ῼ, the maximum power density and the current density were recorded 0.1047 mW/m2 and 21.84 mA/m2, respectively. According to the results of the biological study, strains of bacteria such as Pseudomonas aeruginosa, Acinetobacter schindleri, and Pseudomonas nitroreducens are the ones responsible for producing energy. In addition, final remarks with proposals for the future have been enclosed.